2018
DOI: 10.20517/2394-4722.2018.26
|View full text |Cite
|
Sign up to set email alerts
|

New insights into the role of intra-tumor genetic heterogeneity in carcinogenesis: identification of complex single gene variance within tumors

Abstract: New insights into the role of intra-tumor genetic heterogeneity in carcinogenesis: identification of complex single gene variance within tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 55 publications
(67 reference statements)
0
2
0
Order By: Relevance
“…The determination of a karyotype and genomic hybridization at the molecular level affirms the heterogeneity of cancer cells. DNA sequencing of the cells within the same tumor may differ remarkably to define different subpopulations involving clinical diversity (10,11). Moreover, during tumor development and treatment, it is observed that the plasticity of cancer genomes exhibits itself in the cell-to-cell flexibility of DNA sequence, which can be used for large-scale clinical assistance (12).…”
Section: Contextmentioning
confidence: 99%
“…The determination of a karyotype and genomic hybridization at the molecular level affirms the heterogeneity of cancer cells. DNA sequencing of the cells within the same tumor may differ remarkably to define different subpopulations involving clinical diversity (10,11). Moreover, during tumor development and treatment, it is observed that the plasticity of cancer genomes exhibits itself in the cell-to-cell flexibility of DNA sequence, which can be used for large-scale clinical assistance (12).…”
Section: Contextmentioning
confidence: 99%
“…Moreover, molecular studies, as well as karyotyping and genomic hybridization revealed cancer cell heterogeneity. It was discovered that cells within the same tumor may vary so significantly in terms of DNA sequence to the point of defining different subpopulations, implicating clinical heterogeneity [ 29 , 30 ]. Furthermore, plasticity of cancer genomes manifesting itself in cell-to-cell DNA sequence variability (observed during tumor development and induced by treatment), precludes the achievement of large-scale clinical benefits [ 31 ].…”
Section: Omics: Different Levels Of Gene Expressionmentioning
confidence: 99%